2008
DOI: 10.1016/j.jfms.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium urealyticum urinary tract infection in a cat with urethral obstruction

Abstract: Corynebacterium urealyticum is an uncommon cause of urinary tract infections in cats. However, it is difficult to diagnose and if left untreated it may result in irreversible bladder lesions. C urealyticum is a multiantibiotic-resistant bacterium whose culture requires special care. Risk factors for the occurrence of this infection include urological procedures, foreign bodies, bladder mucosa abnormalities, immuno-suppressed states and antibiotic treatment. This report describes an unusual case of C urealyticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…In humans, most CU-UTIs occur in immunocompromised patients with underlying urological disease and in patients with urological manipulations, previous UTIs, prolonged hospitalisation or after treatment with broad-spectrum antibiotics (Aguado et al 1987, Soriano et al 1990). In the veterinary literature, all animals described as having CU-UTI had similar predisposing factors (Elad et al 1992, Gomez et al 1995, Suarez et al 2002 Bailiff et al 2005, Cavana et al 2008, Briscoe et al 2010, Duffy & Gallagher 2018. The present study supports this observation; among our population, many animals combined several predisposing factors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In humans, most CU-UTIs occur in immunocompromised patients with underlying urological disease and in patients with urological manipulations, previous UTIs, prolonged hospitalisation or after treatment with broad-spectrum antibiotics (Aguado et al 1987, Soriano et al 1990). In the veterinary literature, all animals described as having CU-UTI had similar predisposing factors (Elad et al 1992, Gomez et al 1995, Suarez et al 2002 Bailiff et al 2005, Cavana et al 2008, Briscoe et al 2010, Duffy & Gallagher 2018. The present study supports this observation; among our population, many animals combined several predisposing factors.…”
Section: Discussionsupporting
confidence: 89%
“…Fewer than 15 animals with Corynebacterium urealyticum urinary tract infection (CU-UTI) have been described in the peerreviewed veterinary literature, and the largest case series described only seven animals: five dogs and two cats (Bailiff et al 2005). In previous reports, all animals had a factor that may have predisposed to the CU-UTI (Elad et al 1992, Gomez et al 1995, Suarez et al 2002, Bailiff et al 2005, Cavana et al 2008, Briscoe et al 2010, Raab et al 2015, Duffy & Gallagher 2018. Although the typical clinical presentation of encrusted cystitis due to CU has been previously described in veterinary patients, large case series describing or evaluating predisposing factors, clinicopathological findings, ultrasonographic abnormalities, antimicrobial susceptibility and therapeutic outcome are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…U rinary tract infections (UTIs) caused by Corynebacterium urealyticum are uncommon in dogs and cats. [1][2][3][4][5][6] Treatment is difficult because C. urealyticum is usually resistant to most antibacterial drugs and the administration of glycopeptide antibacterial drugs is often necessary for successful elimination of this microorganism. 1,[4][5][6][7][8] If the infection is complicated by the development of encrustations and stones within the urinary tract, acidification of the urine and surgical resection of calcified plaques and uroliths may become necessary.…”
mentioning
confidence: 99%
“…Many reports have shown that bacterial UTI are more common in older female dogs, indicating that this is an important risk factor (Kivisto et al, 1977;Bush et al, 1978;Thomsen et al, 1986;Cavana et al, 2008;Sidjabat et al, 2009;Hall et al, 2013;Wong et al, 2015). The mean age at diagnosis regardless of sex is approximately 7-8 years (Ling et al, 2001;Cohn et al, 2003).…”
Section: Epidemiology Of Canine Bacterial Urinary Tract Infectionmentioning
confidence: 99%
“…Risk factors for persistent UTI or reinfection in dogs have also been elucidated (Seguin et al, 2003) (Table 1.2). The age and breeds of dogs with recurrent or persistent UTI varies widely (Table 1.3) and may reflect to some extent breed lifespan and changes in popularity of breeds over time (Cavana et al, 2008). Presence or absence of clinical signs is not consistently reported, thus distinguishing between bacterial cystitis and subclinical bacteriuria episodes is often not possible.…”
Section: Epidemiology Of Canine Bacterial Urinary Tract Infectionmentioning
confidence: 99%